Perinatal asphyxia in the term newborn - Roberto Antonucci; Annalisa Porcella; Maria Dolores Pilloni (Hygeia Press di Corridori Marinella, 2014)
Despite the important advances in perinatal care in the past decades, asphyxia remains a severe condition leading to significant mortality and morbidity. Perinatal asphyxia has an incidence of 1 to 6 per 1,000 live full-term births, and represents the third most common cause of neonatal death (23%) after preterm birth (28%) and severe infections (26%). Many preconceptional, antepartum and intrapartum risk factors have been shown to be associated with perinatal asphyxia. The standard for defining an intrapartum hypoxic-ischemic event as sufficient to produce moderate to severe neonatal encephalopathy which subsequently leads to cerebral palsy has been established in 3 Consensus statements. The cornerstone of all three statements is the presence of severe metabolic acidosis (pH < 7 and base deficit ≥ 12 mmol/L) at birth in a newborn exhibiting early signs of moderate or severe encephalopathy. Perinatal asphyxia may affect virtually any organ, but hypoxic-ischemic encephalopathy (HIE) is the most studied clinical condition and that is burdened with the most severe sequelae. The feasibility of providing neuroprotection after HIE has been proven by hypothermia therapy, which is able to reduce the risk of death or major neurodevelopmental disability. Many promising neuroprotective agents might contribute to reduce hypoxic-ischemic brain injury through different mechanisms of action, but further studies are required to confirm their efficacy. The prognosis is dependent on the severity of the perinatal asphyxia. Only a minority of infants with severe HIE survive without handicap.   Proceedings of the International Course on Perinatal Pathology (part of the 10th International Workshop on Neonatology · October 22nd-25th, 2014) · Cagliari (Italy) · October 25th, 2014 · The role of the clinical pathological dialogue in problem solving Guest Editors: Gavino Faa, Vassilios Fanos, Peter Van Eyken